2014
DOI: 10.5817/cp2014-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Media representations and children’s discourses on online risks: Findings from qualitative research in nine European countries

Abstract: Prior research has pointed to cross-national variations in media attention for online risks, which are then mirrored in parental concerns regarding the internet. However, little is known so far about how the discursive environment around opportunities and risks of the internet for children shapes the very context in which children’s own perceptions are developed and their online experiences are situated. The aim of this contribution is threefold: (1) to understand how and to what extent children’s perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…One of the most current studies on parental mediation also indicated that adolescents who reported higher parental mediation were less likely to engage in or experience cyberbullying (Chang et al, 2014). Mascheroni, Jorge, and Farrugia (2014) suggest that "parents seem to use the media as a gateway to discuss the dangers of cyberbullying with their children" (para. 39).…”
Section: Cyber Victimization and Mediation Of Children's Use Of Technmentioning
confidence: 99%
“…One of the most current studies on parental mediation also indicated that adolescents who reported higher parental mediation were less likely to engage in or experience cyberbullying (Chang et al, 2014). Mascheroni, Jorge, and Farrugia (2014) suggest that "parents seem to use the media as a gateway to discuss the dangers of cyberbullying with their children" (para. 39).…”
Section: Cyber Victimization and Mediation Of Children's Use Of Technmentioning
confidence: 99%
“…Regarding the spread of extremist discourse in social media towards ethnic minorities students, it is important to display educative dynamics tending to improve dialogue and to explain to students that the respect to diversity is a basis to enable peaceful relations inside classrooms, communities and, of course, in cyberspace. It is important to provide young students with reliable information to dwell with extremist narratives on the Internet (Mascheroni, Jorge & Farrugia, 2014), to help them understand that those discourses are based on a reductionist and partial notion about social relations, and to recognize that harmonious daily life in US neighborhoods is based on the constructions of sustainable relations among people that do not necessarily resemble their ethnicity or share their religious belief.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to developing opportunities (Kurek, Jose, & Stuart, 2017;Sokolova, 2017;Valkenburg, Koutamanis, & Vossen, 2017), the risks of a negative impact on the psychological health of the Internet user through manipulative influence increase many times. There are increasing risks to face information that threatens the immature psyche and psychological health in general (Boniel-Nissim et al, 2014;Goldstein, 2015;Mascheroni, Jorge, & Farrugia, 2014;Seiler, & Navarro, 2014).…”
Section: Problem Statementmentioning
confidence: 99%